Performances of an Interleaved High Step-Up Converter with Different Soft-Switching Snubbers for PV Energy Conversion Applications - Sheng-Yu Tseng; Hung-Yuan Wang; Chih-Yang Hsu (International Journal of Photoenergy)
This paper proposes an interleaved high step-up converter with different soft-switching snubbers for PV energy conversion applications. For the high step-up converter, interleaved and coupled-inductor technologies are used to reduce output ripple current and increase output power level. Simultaneously, two types of snubbers, a single-capacitor snubber and boost type snubber, are introduced separately into the discussed converters for comparing their performances of conversion efficiency and switching losses. For drawing maximum power from the PV arrays, a perturbation-and-observation method realized with the microcontroller is adopted to achieve maximum power point tracking (MPPT) algorithm and power regulating scheme. Finally, two prototypes of the interleaved coupled-inductor boost converter with a single-capacitor snubber and with boost type snubber are implemented, respectively. The experimental results obtained are used to verify and compare the performances and feasibilities of the discussed converters with different snubbers in PV conversion applications. The experimental results show that the proposed system is suitable for PV energy conversion applications when the duty ratios of switches of the converter are less than 0.5.